PENERAPAN ASAS HUKUM PIDANA ISLAM DALAM PENGGUNAAN CASE MANAGEMENT SYSTEM (CMS) MENURUT INSTRUKSI KEJAKSAAN AGUNG NOMOR 3 TAHUN 2020 (Studi Kejaksaan Negeri Banyuasin, Sumatera Selatan) - Khairunnisa Khairunnisa; Atika Atika; Erniwati Erniwati (Tazir, 2024)
The case handling process at the Prosecutor's Office utilizes information technology in the form of a case management system application. This is a change to the system which previously used a manual system and moved to using Information Technology. This is stated in Attorney General's Instruction Number 3 of 2020. However, in its implementation it has its own obstacles for implementers. The focus of the research is the mechanism for using the case management system application at the Banyuasin District Prosecutor's Office, and how to apply the principles of Islamic criminal law in using the case management system application at the Banyuasin District Prosecutor's Office. This research is empirical normative research, data sources were obtained through direct interviews with research objects, then processed using qualitative descriptive data analysis techniques. The research results show that the mechanism for using the case management system application at the Banyuasin District Prosecutor's Office is in accordance with the SOP that has been determined in the Regulation of the Attorney General of the Republic of Indonesia Number Per-036/A/JA/09/2011, which consists of the stages of pre-prosecution, prosecution, legal action until execution. The application of the principles of Islamic criminal law in the publication system for the case handling process using the CMS application has largely been carried out well and is in accordance with existing general criminal law, however in practice the implementation process in terms of the principle of expediency and the principle of deliberation has not been implemented well. Keywords: Criminal Justice System, Case Management System, Attorney General's Instructions, Principles of Islamic Criminal Law.